Multiple Cerebral, Calcified and Infected Hydatid Cysts Case Report and Literature Review - Kouassi Jean Marie Quenum, Kisito; M, Laghmari; R, Gana; MR, Maaqili; F, Bellakhdar (Journal of Neurological Research And Therapy, 2015)
Calcified and Infected Hydatid Cysts Case Report and Literature Review
Keywords: Hydatid Cysts; Cerebral; Calcified; Case Report; Literature Review